Potensi Tepung Maggot (Hermetia Illucens) sebagai Bahan Pakan Tambahan untuk Memacu Pertumbuhan pada Ayam Pejantan (Kalasan) di Fase Finisher - Muhammad Ridho; Kurniawan Sinaga (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
This study aims to evaluate the effect of adding maggot meal (Hermetia Illucens) as a supplementary feed ingredient on the growth performance of Kalasan male chickens during the finisher phase. A total of 100 chickens were used in this study with a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications, namely P0 (conventional feed without maggot meal), P1 (feed + 5% maggot meal), P2 (feed + 10% maggot meal), and P3 (feed + 15% maggot meal). The observed parameters included feed consumption, body weight gain, and feed conversion ratio (FCR). The results showed that feed consumption increased with the rising proportion of maggot meal, with the highest value recorded in P3 (1081.08 g/bird) and the lowest in P0 (894.04 g/bird). The highest body weight gain was also achieved in P3 (487.96 g/bird), while P0 had the lowest weight gain (410.02 g/bird). However, the best FCR values were obtained in P1 (2.09) and P2 (2.10), indicating more optimal feed efficiency at moderate maggot meal supplementation levels. Therefore, adding maggot meal at a 10% level (P2) is recommended as the most effective option, as it can increase body weight while maintaining balanced feed efficiency.